Gymnastics basics - Traetta, John; Traetta, Mary Jean; Gow, Bill; Carter, Don; Knudsen, Arvid (Englewood Cliffs, N.J. Prentice-Hall, 1979)
Text and photographs introduce basic gymnastic techniques.
Includes index.
Keywords: Gymnastics -- Juvenile literature; Gymnastics